ANALISIS YURIDIS TERHADAP PENATAAN RUANG KAWASAN PESISIR PANTAI MATTIROTASI DALAM MENUNJANG KEPARIWISATAAN DI KOTA PAREPARE - Firmansyah (Madani Legal Review, 2019)
This research was conducted by examining spatial planning patterns and community activities that were obstacles and problems in the region. The purpose of this study is to arrange the existing space in the Mattirotasi Beachfront Area, including existing and permitted activities based on the policy and the existing constraintsandproblems.The results of the study showed that there were problems and problems that existed in the Mattirotasi Beach Area, including solid waste, street vendors, area parking areas, maintenance, area management and activities of local communities (fishermen). While for landscape planning, the regional spatial plan is divided into 4 segments with 3 core segments and 1 buffer segment, for planned circulation and access to the area and between segments planned for 2 lanes namely primary and secondary lines.